(untitled) (Libellarium: journal for research in the field of information and related sciences, 2026)
This report outlines the key discussions from a workshop on the gaps and challenges faced by Diamond Open Access (OA) journals. Members of the CRAFT-OA project held the workshop at the OPERAS conference 2024 in Zadar, Croatia. The workshop focused on three areas: 1) community standards, 2) technical aspects, and 3) sustainability. The workshop highlighted how existing and emerging publishing standards are influenced by and, simultaneously, impact Diamond OA communities; the need to bridge technical gaps by encouraging community adoption of technical standards in particular; and the sustainability challenges posed by financial constraints and the perceived lack of prestige of Diamond OA journals. In three working groups, participants of the workshop identified challenges and discussed strategies and pathways to overcome these challenges, such as raising awareness of standards, enhancing visibility, and improving funding mechanisms to ensure the long-term viability of Diamond OA journals.